2005
DOI: 10.1016/j.cub.2005.05.055
|View full text |Cite
|
Sign up to set email alerts
|

STIM Is a Ca2+ Sensor Essential for Ca2+-Store-Depletion-Triggered Ca2+ Influx

Abstract: Ca(2+) signaling in nonexcitable cells is typically initiated by receptor-triggered production of inositol-1,4,5-trisphosphate and the release of Ca(2+) from intracellular stores. An elusive signaling process senses the Ca(2+) store depletion and triggers the opening of plasma membrane Ca(2+) channels. The resulting sustained Ca(2+) signals are required for many physiological responses, such as T cell activation and differentiation. Here, we monitored receptor-triggered Ca(2+) signals in cells transfected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

71
2,198
3
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,933 publications
(2,286 citation statements)
references
References 27 publications
71
2,198
3
14
Order By: Relevance
“…STIM 1 and Orai 1 puncta formation directly correlates to SOCE activity (Liou et al 2005). Similar to the glomerulus, immunofluorescence images also indicate that the expression level of STIM 1 and Orai 1 decreased in aged rat GMCs (Fig.…”
Section: Stim 1 and Orai 1 Contribute To Soce Activity In Gmcsmentioning
confidence: 99%
See 1 more Smart Citation
“…STIM 1 and Orai 1 puncta formation directly correlates to SOCE activity (Liou et al 2005). Similar to the glomerulus, immunofluorescence images also indicate that the expression level of STIM 1 and Orai 1 decreased in aged rat GMCs (Fig.…”
Section: Stim 1 and Orai 1 Contribute To Soce Activity In Gmcsmentioning
confidence: 99%
“…The N-terminus of STIM 1 is located in the lumen of the endoplasmic reticulum (ER) and functions as a Ca 2+ sensor. The C-terminus of STIM 1 is located in the cytosol and activates SOCE upon store depletion by interacting with the plasma membrane Orai 1 Liou et al 2005;Roos et al 2005). Knockdown of STIM 1 expression using specific small interfering RNA (siRNA) significantly reduced SOCE in a number of cell types, whereas STIM 1 overexpression modestly enhanced SOCE (Feske et al 2006;Roos et al 2005;Williams et al 2002;Liou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, two major SOCE components have been identified: the Stromal Interacting Molecule 1 (STIM1) [20][21][22] predominantly located in the ER membrane and that senses the luminal Ca 2+ concentration, and the Ca 2+ channel Orai1 (also known as CRACM; [23][24][25]). Upon Ca 2+ store depletion, STIM1 oligomerizes, translocates close to the plasma membrane and aggregates into punctate structures [2,21,26].…”
Section: Introductionmentioning
confidence: 99%
“…Upon Ca 2+ store depletion, STIM1 oligomerizes, translocates close to the plasma membrane and aggregates into punctate structures [2,21,26]. The interaction between STIM1 and Orai1 leads to channel opening and Ca 2+ entry [23,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…A similar conclusion was independently reached by others [15][16][17][18], who in addition showed that ORAI1 increased CRAC currents if expressed with the CRAC activator STIM1. STIM1 has been previously shown to mediate CRAC activation after Ca 2+ store depletion [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%